Kajian Kebutuhan Pelayanan Home Care Pada Pasien Stroke Lanjut Usia - Ismiyati, Ismiyati; Akhmadi, Akhmadi; Haryani, Haryani (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2009)
Please refer to the file